Quantitative taxonomy of flower color in Gladiolus × gandavensis cultivars - Chao Liu; Mi Yin; Wei-Ting Lin; Xian-Hua Xiong; Qiu-Xu Tang; Yu-Tong Wang; Hong-Dan Li (Acta Scientiarum Polonorum: Hortorum Cultus)
Gladiolus × gandavensis is one of the world’s four famous cut flowers. Flower color is an important basis for the classification of Gladiolus × gandavensis. To define the flower color of Gladiolus × gandavensis more scientifically, twenty-three Gladiolus × gandavensis horticultural cultivars were studied for flower color phenotypes to provide a preliminary phenotypic quantitative basis for the determination of the affinity of unknown cultivars in the species and provide a scientific basis for the definition of flower color in the classification process. Based on the results of the RHSCC colorimetric card and colorimeter, the 23 Gladiolus × gandavensis cultivars were classified into six flower color categories, i.e. white, pink, purple, greenish-yellow, orange, and red. Clustering analysis further verified the above classification results according to the flower color, indicating that the two have good correspondence. At the same time, the characteristics of the distribution of the parameters of the CIELab color system of Gladiolus × gandavensis were analyzed and preliminarily determined the distribution range of the phenotypic parameters of each color group, and the results filled a gap in the study of the floral phenotype of Gladiolus × gandavensis.